On the Language of Student Teachers' Professional Vision: How Do Pre-Service EFL Teachers Comment on Classroom Videos of Pupil Engagement? - Miroslav Janík; Eva Minaříková; Tomáš Janík; Zuzana Šmideková (Karolinum Press, 2022)
Teacher's professional vision is a well-researched concept that highlights the importance of noticing salient issues in classroom situations and reasoning about them. This paper aimed to investigate pre-service teachers' professional vision of pupil engagement: what student teachers notice in classroom videos regarding pupil engagement and how they verbalize it. The data was collected using interviews with classroom videos as prompts. 20 English as a foreign language pre-service teachers participated in the study. The data was analysed using qualitative content analysis and word clouds. The results suggest that pupil engagement is observed on three levels: behavioural, cognitive, and emotional, and it is seen in connection with classroom factors influencing it; the most mentioned one being teacher actions. To verbalize their noticing of pupil engagement, student teachers used wors and phrases that describe engagement directly (such as "participate", "enjoy", "respond") or indirectly, for example through descriptions of actions ("raising hands") or suggestions of cognitive involvement with the content ("know" or "remember"). Understanding how student teachers talk about pupil engagement can help us tease out important points in discussions during teacher education programmes and, in doing so, aid the pre-service teachers in framing their noticing and developing their professional vision.